PERBEDAAN PEMBERIAN PIJAT PERINEUM TERHADAP DERAJAT LASERASI PERINEUM PADA IBU BERSALIN DI PRAKTEK BIDAN MANDIRI KOTA PEKANBARU - Febby Adha Firdausia; Berliana Irianti; Nurhapipa; Een Husanah; Octa Dwienda Ristica (Institut Kesehatan dan Teknologi Al Insyirah, 2025)
Perineal laceration is a common complication of vaginal delivery that can cause reproductive organ dysfunction and bleeding. As many as 85% of women who give birth vaginally may experience perineal laceration. One non-invasive intervention that can be performed to prevent this is perineal massage. This study aims to determine the difference in the degree of perineal laceration between mothers who received perineal massage and those who did not. The research method used a quasi-experimental design with a posttest-only control group approach. The sample consisted of 26 mothers who gave birth, divided into two groups, namely the intervention group (given perineal massage) and the control group (without perineal massage). Data collection was carried out at PMB Rosita and Ernita Midwife Clinic in Pekanbaru City from 24 April to 23 May 2025. Data analysis used the Mann-Whitney test. The results showed that in the intervention group, the majority of the 13 pregnant women who received perineal massage, 4 (30.8%) experienced grade I, 1 (7.7%) experienced grade II, and 8 (61.5%) had no lacerations. The Mann-Whitney test results showed a p-value of 0.001 (p < 0.05), indicating a significant difference between the intervention and control groups in terms of the degree of perineal laceration. Conclusion: Perineal massage as a non-pharmacological alternative has been proven to significantly reduce the degree of perineal laceration in mothers giving birth. It is hoped that perineal massage can become one of the interventions applied in maternal health services to prevent perineal rupture in mothers giving birth